Interpretation of Sectoral Standard Requirements and Test Methods for Orthopaedic Surgical Navigation Equipment Employing Robotic Technology - TANG Qiaohong; MENG Xiangfeng; WANG Hao; LI Shu (Xiehe Yixue Zazhi)
In recent years, robot-assisted technology has become increasingly sophisticated in the field of orthopedic surgical navigation. To ensure surgical safety and protect patient rights, corresponding products must undergo rigorous and standardized pre-market quality evaluations. In 2023, the National Medical Products Administration issued the sectoral standard YY/T 1901-2023 Requirements and Test Methods for Orthopaedic Surgical Navigation Equipment Employing Robotic Technology. This standard specifies the performance requirements for robotic orthopedic surgical navigation systems across ten key aspects: general requirements, robotic arm positioning device performance, tracking device performance, system performance, installation repeatability, protective functions, orthopedic powered surgical instruments, liquid cooling, positioning accessory requirements, and software requirements. Additionally, it standardizes quality evaluation methods, providing significant guidance for advancing robotic technology, accelerating product market entry, and strengthening regulatory oversight. This article analyzes the key components of the standard to facilitate better qualityassessment of products and promote high-quality development within the industry.